Halal Label Perception Towards Purchase Decision of Imported Processed Food Products for Muslim Generation Z - Nursyamsiah, Tita; Syahida Rohmah, Naila; Hasanah, Qoriatul (IQTISHODUNA: Jurnal Ekonomi Islam, 2022)
Indonesia is presently experiencing a growing influx of imported processed food products distributed within its borders. However, not all of these products are labeled, which has led to a situation where Muslim consumers must exercise increased caution during purchase to ensure their adherence to halal standards and suitability for consumption. This study examined the effect of religiosity, reference groups, income, lifestyle, and perception of halal label on the purchasing decision of Muslim. Data were collected from 100 respondents of Muslim Generation Z residing in Bogor Regency. Descriptive analysis methodology was employed, and the data was analyzed through the application of Structural Equation Modeling-Partial Least Square (SEM-PLS). The result showed that the reference group, income, lifestyle, and perception of halal label positively and significantly affected purchasing decision for imported processed food.